2015
DOI: 10.1590/0100-2945-211/14
|View full text |Cite
|
Sign up to set email alerts
|

DIETARY FIBRE CONTENT, PHENOLIC COMPOUNDS AND ANTIOXIDANT ACTIVITY IN SOURSOPS (Annona muricata L.)

Abstract: -healthy eating is associated with the consumption of fruits, which are notable for their beneficial effects on human health. The aim of this study was to evaluate the proximate composition, composition of fibers and components with antioxidant activity in soursops varieties Crioula, Lisa and morada of physiological maturity (Pm) and mature (m). The protein, lipid and moisture contents did not differ between soursop varieties, but the ash contents were higher in the morada-Pm (0.56%±0.03) and the Morada-M (0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
6
1
1
Order By: Relevance
“…Formosum leaves by ultrasound than conventional method by heating. The level of EPPs in the methanol extract of soursop pulp found in this study was almost two times higher than reported by other authors in soursop pulp, who have reported values from 1.86 g GAE 100 g -1 DM (MORENO-HERNÁNDEZ et al, 2014;SIQUEIRA et al, 2015). The values of antioxidant capacity determined by DPPH…”
contrasting
confidence: 71%
“…Formosum leaves by ultrasound than conventional method by heating. The level of EPPs in the methanol extract of soursop pulp found in this study was almost two times higher than reported by other authors in soursop pulp, who have reported values from 1.86 g GAE 100 g -1 DM (MORENO-HERNÁNDEZ et al, 2014;SIQUEIRA et al, 2015). The values of antioxidant capacity determined by DPPH…”
contrasting
confidence: 71%
“…The more soursop puree, the greater the total dietary fiber value (Table 1). According to Michaelsen et al (2009) and Siqueira et al (2015), the dietary fiber content on soursop puree is of 3.72-5.76%, while that of horn plantain which is 2.3%. The ratio of 1:3 produces the highest total dietary fiber of 5.82±0.08%.…”
Section: Phase I Methodsmentioning
confidence: 99%
“…Em termos nutricionais, a graviola apresenta conteúdo médio de umidade de 80%, seguido de carboidratos totais de 4,7%, fibras totais com relevância para as fibras insolúveis de 3,6%. O teor médio de compostos fenólicos totais é de 244 mg de ácido gálico por grama de fruta (SIQUEIRA et al, 2015). Também é uma boa fonte de vitaminas do complexo B, sendo de extrema importância para o metabolismo de gorduras, carboidratos e proteínas, adicionando ao cardápio vitaminas e minerais, além de ser ótimo para a saúde (JUNQUEIRA; JUNQUEIRA, 2014).…”
Section: Aspectos Gerais Sobre a Graviolaunclassified